Cytotoxic investigation of crude extracts and isolated compounds from Ruta angustifolia Pers. leaves and effects of chalepin on the expression of selected cancer-related proteins in human lung carcinoma cells A549 / Jaime Stella Moses Richardson - Jaime Stella , Moses Richardson (2018)
Plants have been a major source of inspiration in developing novel drug compounds for the treatment of various diseases that afflict human beings worldwide. Ruta angustifolia Pers. known locally as garuda, has been traditionally used for various medicinal purposes. One of the common ethnopharmacological uses includes usage in treatment of cancer by the local chinese community in Malaysia and Singapore. The methanol and fractionated extracts of R. angustifolia were tested with sulforhodamide (SRB) cytotoxicity assay against HCT-116, A549, Ca Ski and MRC5 cell lines. The chloroform extract (without chlorophyll) exhibited the highest cytotoxicity with IC50 value of 8.8 ± 0.32 μg/mL. The chemical investigation of the plant has resulted in isolation of 12 compounds. Among the compounds, chalepin (dihydrofuranocoumarin) exhibited the best cytotoxicity against A549 cell line with an IC50 value of 8.69 ± 2.43 μg/mL (27.64 μM) and was futher tested for induction of apoptosis in A549 cells. The morphological changes in the cell were observed via phase contrast microscopy and Hoechst/PI fluorescent staining. Phosphatidylserine externalisation and DNA fragmentation was perceived. Mitochondrial mediated apoptosis exhibits attenuation of mitochondrial membrane potential and increase in ROS production also activation of caspase 9 and 3. Western blot analysis also showed upregulation of p53, Bax and Bak while the anti-apoptotic proteins Bcl-2, survivin, XIAP, Bcl-XL, cFLIP decreased in a time-dependent manner in A549 cells treated with chalepin. PARP was found to decrease. These findings indicated that chalepin-induced cell death involving the intrinsic mitochondrial pathway. Death receptors (DR4 & DR5) were upregulated and caspase 8 showed activation in a dose and time dependant manner showed the initiation of extrinsic pathway. Activated caspase 8 induced cleavage of BID to tBID, which would initiate a mitochondrial dependent or independent apoptosis. The cell cycle analysis showed that cell cycle was arrested at the S phase. Inhibition of cyclins (cyclin D1 and E) and cyclin dependant kinases (CDK2, CDK4), upregulation of inhibitors of CDKs (p21 and p27) and the hypophosphorylation of Rb protein corresponds to a cell cycle arrest at the S phase. Chalepin also suppressed the NF-kB pathway by inhibition of phosphorylation of IkBa, inhibition of phosphorylation of p65 and obstructed the translocation of p65 to nucleus. The phosphorylation of EGFR receptor was inhibited by chalepin and thus further downregulated the downstream MAPK-ERK pathway and Akt/mTOR pathway. Upregulation of SAPK/JNK and p38 protein was observed. Chalepin also exhibited suppression in inhibitors of apoptosis (MCL-1, CIAP-1, and CIAP-2), STAT-3, COX-2 and c-myc. Metastatic proteins such as ICAM-1 and VEGF was suppressed by chalepin suggesting that it has anti-metastatic property. An antimetastatic investigation on methanol and chloroform extracts conducted showed that both the extracts possessed excellent anti-invasion and anti-migration property, prevent cell attachment, inhibit cell motility via wound closure assay, prevent cell adhesion by inhibiting the cell adhesion molecules and inhibit proliferation. Proteolytic enzyme (MMP 2) showed suppresion through gelatin zymography studies. Chalepin however showed to possess moderate anti-metastatic property in these assays. Our findings suggest the potential of this compound to be further developed as an excellent chemotherapeutic agent.